Detecting hidden patterns in the dynamics of play in team sports - Camerino, O.; Jonsson, G. K.; Sanchez-Algarra, P.; Anguera, M. T.; Lopes, A.; Chaverri, J. (Mixed methods research in the movement sciences: Case studies in sport, physical education and dance, 2014)
Case Study 2.1: Temporal pattern analysis and its applicability in sport: illustrative data from an attack session in rugby. Case Study 2.2: Influence ofthe use ofspace on the dynamics of play in basketball. Case Study 2.3: The dynamics of play and defensive systems in handball. One important area in the field of sports science concerns the need to explain, predict and even control the factors that determine success in competitive team sports. This is a key aspect when it comes to helping coaches to make decisions regarding the management of both training and competitive situations, as weIl as for increasing player motivation in high-level performance. Recently, sports performance has begun to be considered as a dynamical system, and attempts have been made to apply concepts from dynamical systems theory to the study of emergent game structure and tactical patterns in team sport. In this regard, understanding profiles of play and how they are leamt cognitively in team sports is a new and interesting approach to the optimization of effective performance. Given the above there is a growing need for the rigorous collection of sport related data that provide empirical evidence about the complex reality they refer to. Key aspects in this regard include the presence of regularities that are not detectable through visual inference or traditional methods of data analysis, as weIl as the lack of standard observation instruments and the priority need to develop powerful, computerized coding systems, all of which must form part of an approach that is suitable for natural exercise environments.